"Our Country Is a Freedom-Loving Country": The Spreading Virus as Metaphor for "People on the Move". (3rd April 2022) - Gurnham, David
ABSTRACT: Although Covid-19 has been framed using all manner of metaphors, an as-yet under-examined question is how the spreading virus might itself serve as a metaphor and what purpose this might serve. The article redresses this deficit by identifying shared experiences of the mobile virus as the basis for a metaphorical framework for evaluating and judging human behavior, including alleged rule-breaking, during the pandemic. The article traces the appearance of the metaphor spreading across a broad spectrum of sources that includes political speech, the reporting of crime in prosecutorial and local media sources, judicial opinion and poetry. We observe in some limited contexts a straightforward metaphoric transfer or substitution between mobile people and the mobile virus. In a greater number and variety contexts, we find instead more subtle signs of the metaphor: the censuring of bad behavior and the justifying of coercive treatment using the metonymic elements of viral spread: its characteristic unpredictability, speed, agility, irrepressibility, and relentlessness.